Optimal Fiscal Spending and Reserve Accumulation Policies under Volatile Aid - Moldovan, Ioana (IMF Working Papers; Working Paper ;, 2019)
This paper assesses the optimal setting of fiscal spending and foreign exchange rate intervention policies in response to volatile foreign aid, in a small open economy model that incorporates typical features of low-income countries. Within a class of policy rules, it jointly considers the optimal aid spending and international reserve accumulation policies. The results show that it is optimal to adjust government spending gradually in response to unpredictable fluctuations in aid, while partially accumulating foreign exchange reserves to offset Dutch disease effects. Also, allocating relatively more of the government spending to productive public investment, and less to government consumption, is welfare improving.